A Systematic Literature Review of Machine Learning for Endurance Running Performance Prediction - Solang, Efraim William; Linawati, Linawati; Manuaba, Ida Bagus Gede; Setiawan, I Nyoman (Sinkron : jurnal dan penelitian teknik informatika, 2026)
This study systematically reviews the application of machine learning methods for predicting running performance, with particular emphasis on short-middle distance events such as the 5 km. Although machine learning based performance prediction has been widely explored in endurance sports, a comprehensive review synthesizing models, predictors, and pipelines across running distances remains limited. The review followed the PRISMA 2020 framework. Articles published between 2020 and 2025 were retrieved from ScienceDirect, Google Scholar, and PubMed using predefined keyword combinations related to machine learning and running performance. Studies were included if they focused on running (excluding cycling, triathlon, or other sports), applied predictive modeling, and reported model evaluation metrics. A total of 26 studies met the inclusion criteria and were assessed using quality appraisal criteria inspired by TRIPOD and QUADAS-2. The analysis identified four main research themes: (1) application of machine learning models for running performance prediction, (2) physiological and anthropometric predictors, (3) non-physiological and contextual factors, and (4) personalized athlete training and monitoring. Ensemble learning models (Random Forest, XGBoost, LightGBM) consistently outperformed traditional linear regression by capturing non-linear interactions, while deep learning approaches (LSTM, GRU) demonstrated strong capability in modeling temporal training dynamics. A generalized machine learning pipeline for running performance prediction was also synthesized. This review contributes a structured framework that integrates modeling approaches, predictor categories, and evaluation strategies, and highlights research opportunities for explainable and personalized prediction systems, particularly for 5 km running performance.